2000
DOI: 10.1128/aac.44.7.1911-1916.2000
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B Resistance and Membrane Fluidity in Kluyveromyces lactis Strains

Abstract: The membrane fluidity of reduced-amphotericin B (AmB)-sensitivity Kluyveromyces lactis mutant strain is higher than that of the wild-type K. lactis strain. After culture of the K. lactis and K. lactis mutant cells in the presence of subinhibitory doses of AmB (10 and 125 mg/liter, respectively), the plasma membranes of both yeast strains also showed a higher fluidity than did those of control cells. High membrane fluidity was associated with changes in the structural properties of the membranes. Culture of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Indeed, changes in the structural properties of the K. lactis membrane (decreased sterol/phospholipid ratio, the decreased saturated fatty acid/monounsaturated fatty acid ratio) could explain the higher membrane fluidity, which represents higher resistance of the K. lactis yeast to several drugs compared with its Klpdr16⌬ mutant. Our results thus support the observations of Mishra et al (2008), who found increased membrane fluidity in fluconazole-resistant C. albicans clinical isolates from diabetic patients, and those of Younsi et al (2000), explaining higher membrane fluidity with changes in its lipid composition, representing a process of metabolic resistance of the K. lactis yeast to amphotericin B. The precise molecular function of KlPdr16p in providing protection against azole antifungals is not known yet and requires further experimentation.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, changes in the structural properties of the K. lactis membrane (decreased sterol/phospholipid ratio, the decreased saturated fatty acid/monounsaturated fatty acid ratio) could explain the higher membrane fluidity, which represents higher resistance of the K. lactis yeast to several drugs compared with its Klpdr16⌬ mutant. Our results thus support the observations of Mishra et al (2008), who found increased membrane fluidity in fluconazole-resistant C. albicans clinical isolates from diabetic patients, and those of Younsi et al (2000), explaining higher membrane fluidity with changes in its lipid composition, representing a process of metabolic resistance of the K. lactis yeast to amphotericin B. The precise molecular function of KlPdr16p in providing protection against azole antifungals is not known yet and requires further experimentation.…”
Section: Discussionsupporting
confidence: 90%
“…A less fluid membrane has also been shown to be a factor influencing the resistance of Staphylococcus aureus to the cat- (38). It is also known that the increased levels of monounsaturated fatty acids in the membrane phospholipid influence the overall decrease in the membrane molecular order (38). These findings indicate the significant roles played by unsaturated phospholipids and membrane fluidity in antibiotic or antimicrobial peptide association with membranes and consequently in resistance mechanisms.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast, the larger amounts of longer and saturated PGs in the sensitive L. monocytogenes B73 and 412 strains may enhance membrane insertion by bacteriocin and thus increase sensitivity. A less fluid membrane has also been shown to be a factor influencing the resistance of Staphylococcus aureus to the cat- (38). It is also known that the increased levels of monounsaturated fatty acids in the membrane phospholipid influence the overall decrease in the membrane molecular order (38).…”
Section: Discussionmentioning
confidence: 99%
“…A weaker insertion ability of AMPs into unsaturated phosphatidylglycerol could point to the role of increased amounts of unsaturated fatty acids and increased membrane fluidity in resistant strains. Similarly it has been observed that Kluyveromyces lactis mutant cells with reduced amphotericin B sensitivity have a higher unsaturated fatty acid-to-saturated fatty acid ratio than do wild type K. lactic cells (Younsi et al, 2000). Hence membrane fluidity could be an important contributing factor to class IIa bacteriocins and AMPs resistance by affecting the insertion into membranes and consequently the formation and stability of the pores.…”
Section: Discussionmentioning
confidence: 95%